STUDENTS’ ENGAGEMENT IN ENGLISH LANGUAGE COURSE - Hasdina, Niken; Sofyawati, Eva Devi; Dewi, Sinta; Oktarina, Hanifah (IPI Garut Press, 2024)
This study aims to analyze the types of student engagement shown by students in the English Language Course. The second objective is to find out the factors that influence student engagement. This research was conducted on 8th grade students at Garut High School. To achieve these objectives, qualitative research with a case study design was used with observation and interview data collection techniques. The sample for this study consisted of 35 students. Out of all the participants, three participated in the interview. The results showed that there were three types of student engagement found, namely cognitive engagement, behavioral engagement, and affective engagement. It was found that the most dominant type was cognitive engagement. The results also show that the five factors presented by Fredricks, Blumenfeld, and Paris (2004) influence student engagement in English language courses. The five factors are: school level, teacher support, peers, classroom structure, and task characteristics.